Histopathological patterns and biological characteristics of ameloblastoma: A retrospective cross-sectional study - Bwanbale,Phenehas; Pollard, Suzanne L.; Sekitoleko, Isaac; Namazzi, Esther; Kalyesubula, Robert (Trials, 2021)
COPD is a leading cause of death globally, with the majority of morbidity and mortality occurring in low- and middle-income country (LMIC) settings. While tobacco-smoke exposure is the most important risk factor for COPD in high-income settings, household air pollution from biomass smoke combustion is a leading risk factor for COPD in LMICs. Despite the high burden of biomass smoke-related COPD, few studies have evaluated the efficacy of pharmacotherapy in this context. Currently recommended inhaler-based therapy for COPD is neither available nor affordable in most resource-limited settings. Low-dose theophylline is an oral, once-a-day therapy, long used in high-income countries (HICs), which has been proposed for the management of COPD in LMICs in the absence of inhaled steroids and/or bronchodilators. The Low-dose Theophylline for the Management of Biomass-Associated COPD (LODOT-BCOPD) trial investigates the clinical efficacy and cost-effectiveness of low-dose theophylline for the management of biomass-related COPD in a low-income setting.LODOT-BCOPD is a randomized, double-blind, placebo-controlled trial to test the efficacy of low-dose theophylline in improving respiratory symptoms in 110 participants with moderate to severe COPD in Central Uganda. The inclusion criteria are as follows: (1) age 40 to 80 years, (2) full-time resident of the study area, (3) daily biomass exposure, (4) post-bronchodilator FEV1/FVC below the 5th percentile of the Global Lung Initiative mixed ethnic reference population, and (5) GOLD Grade B-D COPD. Participants will be randomly assigned to receive once daily low-dose theophylline (200 mg ER, Unicontin-E) or placebo for 52 weeks. All participants will receive education about self-management of COPD and rescue salbutamol inhalers. We will measure health status using the St. George’s Respiratory Questionnaire (SGRQ) and quality of life using the EuroQol-5D (EQ-5D) at baseline and every 6 months. In addition, we will assess household air pollution levels, serum inflammatory biomarkers (fibrinogen, hs-CRP), and theophylline levels at baseline, 1 month, and 6 months. The primary outcome is change in SGRQ score at 12 months. Lastly, we will assess the cost-effectiveness of the intervention by calculating quality-adjusted life years (QALYs) from the EQ-5D.
Keywords: Ameloblastoma; Biological behaviour; Histopathological patterns